Determinants of Dividend Policy and Investment Opportunity Set in Manufacturing Companies Listed on The Indonesia Stock Exchange - Devi, Ni Luh Nyoman Sherina; Manuari, Ida Ayu Ratih (AIBPM Publisher, 2023)
The company's finance decision and dividend policy are two related issues that cannot be separated. When deciding on the value of the company as the primary goal of future expenditures, the IOS offers a more thorough direction. This research seeks to determine the impact of liquidity, activity, and profitability on dividend policy and IOStings in manufacturing businesses listed on the Indonesia Stock Exchange. All manufacturing businesses registered on the Indonesian Stock Exchange in 2018–2020 comprise the population of this study. Using the purposive sampling method, a total sample of 40 manufacturing enterprises for the observation period of 2018-2020 was obtained. Partial Least Squares (PLS) is used and this study's conclusion, dividend policy is unaffected by liquidity. The dividend policy is significantly and positively impacted by profitability. The IOS is unaffected by liquidity. The IOS is unaffected by activity. Profitability significantly and positively influences the IOS. The IOS is significantly and positively affected by dividend policy.